Detection of tdh and trh virulence genes, antibiotic resistance and genetic diversity of Vibrio spp. isolated from shrimp - Gargouti, Saifedden Ayad (2016)
Vibrio parahaemolyticus and Vibrio alginolyticus are considered among gastrointestinal pathogens. Vibrios are a common causative agent of seafood-borne illness in tropical and subtropical countries including Malaysia, where the temperature is optimal for their growth. Although Vibrio parahaemolyticus and Vibrio alginolyticus not documented well, the majority of illness is self-limiting, treatment is not necessary. Multiplex PCR, Antibiotic resistance and RAPD-PCR were used to detect and characterize of 60 samples of shrimp purchased from the local supermarkets in Selangor, Malaysia were examined for pathogenic and non-pathogenic genes (tdh, trh, and toxR genes). A total of 56 (93.3%) out of 60 samples were found positive for V. parahaemolyticus. The density of screened samples ranged from 62 MPN/g to >110,000 MPN/g. About 50% of positive samples contained >10⁴ MPN/g of V. parahaemolyticus. Multiplex polymerase chain reaction (PCR), was conducted to determine pathogenic and non-pathogenic genes, estimated that 93.33% of samples were positive for the toxR gene at band 368 bp. The significant result comes with 2 samples of V. alginolyticus were isolated on CHROMTM Vibrio agar. Both samples were positive for the tdh, trh, and toxR genes at bands 251, 484, and 368 bp, respectively. The 16S ribosomal DNA sequence (1.5 kb) full-length was also performed. The result showed 99% similarity to V. alginolyticus strain ATCC 17749. Thirty isolates were tested for their susceptibility to 14 different antibiotics. Vibrio isolates were resistant to ampicillin (80%), amoxicillin–clavulanic acid and cefotaxime (50%), ceftazidime (46.7%), cefepime (33.3%). However, the isolates were highly susceptible to imipenem (100%), and piperacillin and gentamicin (96.7%). Approximately 55% of the isolates showed a multiple antibiotic resistance (MAR) index of >0.2, thereby indicating the high risk of sources where these isolates originated. Randomly amplified polymorphic DNA–PCR (RAPD-PCR) was performed on 30 samples to determine the genetic diversity among V. parahaemolyticus and V. alginolyticus isolates. Two primers, namely, OPAR-03 (5′-GTGAGGCGCA-3′) and OPAR-10 (5′-TGGGGCTGTC-3′), showed the most satisfactory results and were selected for this study. Primers OPAR03 and OPAR10 produced 2–10 and 2–8 bands, respectively, and their amplicon sizes ranged within 200–2000 bp. A total of 19 RAPD patterns reflected the high genetic diversity among the V. parahaemolyticus isolates obtained from shrimp samples. The incidence of Vibrio parahaemolyticus could be expected and natural. This study is the first to report about the expression of tdh and trh toxic genes of V. parahaemolyticus in V. alginolyticus. RAPD-PCR analysis showed that V. parahaemolyticus and Vibrio alginolyticus are exhibited a high level of genetic diversity. The result stressed the importance of Vibrio to food safety and public health and an economic impact.